PROSES KOMUNIKASI PADA EXTENDED FAMILY DALAM MEMBANGUN KONSEP DIRI ANAK - Mary Nuriko Tresia Sucipto, Sisilia; Luqman, Yanuar (Interaksi Online, 2022)
The role of parents in caring for and controlling children sometimes cannot be done ideally because of various reasons, so the obligation requires the involvement of extended families for helping the children to develop well. However, living with an extended family means that children are faced with more diverse backgrounds and communication patterns and they need to study communication interactions with each family member to find out how they should behave. In addition, the communication process that takes place in the family contributes to the process of developing the self-concept of the children who live in it. The purpose of this research is to determine communication within the extended family and its role in the process of building the self-concept of the children who live in it. The type of research is descriptive qualitative. The research uses family communication pattern theory dan self-disclosure theory. Research’s subject is the extended family that consist of a 10-15 years old child; parents; and kin that lives together at this moment. The research uses depth interview as the data collection technique. The results of the research states that the communication that occurs in the extended family is unique because family members learn to deal with people with diverse backgrounds and ways of communicating. The children create knowledge schemas about their relationships with family members through the communication they do in everyday life. Family members who become significant others for children have a big role in the process of developing children’s self-concept because their opinions, responses, teachings, and suggestions are very much cared for by the children. Also, the extended family environment plays an important role in providing basic knowledge for the children. A good extended family environment encourage the children develop positive self-concept and vice versa